A Case of Aspiration Pneumonia Caused by Cerebrospinal Fluid Leaks Associated with Delayed Identification of Iatrogenic Skull Base Injury during Endoscopic Sinus Surgery. (9th April 2021) - Anzai, Takashi; Baba, Akira; Ito, Shin; Suzuki, Yo; Tajima, Shori; Hara, Satoshi; Takata, Yusuke; Matsumoto, Fumihiko; Ikeda, Katsuhisa
Abstract : Cerebrospinal fluid (CSF) leaks associated with endoscopic sinus surgery (ESS) are a rare complication affecting approximately 0.09% of patients. Although meningitis is a well-known complication of CSF leaks, the case we present is a rare and cautionary case of CSF leakage associated with ESS leading to aspiration pneumonia. A 43-year-old man with CSF leaks after ESS was referred to our hospital. After the operation, sometimes, he reported having a serous nasal discharge from the right side when he bent over, and he woke up choking on something every day. He also experienced headache, fever, fatigue, and cough. Interestingly, chest computed tomography (CT) showed a consolidation and ground-glass opacity in the posterior segments of the right upper lobes and superior segments of the bilateral lower lobes. These CT imaging findings were similar to those of aspiration pneumonia in bedridden patients who are always in a supine position. These findings suggest that CSF caused aspiration pneumonia. To the best of our knowledge, no case of aspiration pneumonia caused by CSF during endoscopic sinus surgery has been reported until now. If a patient with CSF leakage after ESS experiences fever, cough, or fatigue, physicians should consider aspiration pneumonia in addition to meningitis.